Saadoe’ddin Djambek's Thoughts on Calculating the Beginning of the Hijri Month - Marwadi, Marwadi; Mughni Labib (Sekolah Tinggi Agama Islam Negeri Majene, 2025)
The determination of the beginning of the Hijri month is important for Muslims as the basis for performing several religious rituals. There are two major schools of thought that are the source of debate in determining the beginning of the Hijri month, namely the rukyat school and the hisab school. Hisab is divided into hisab urfi and hisab hakiki. Hisab hakiki is further categorised into hisab hakiki taqribi, hisab hakiki tahqiqi, and hisab hakiki kontemporer. One of the data sources for hisab hakiki kontemporer is the Nautical Almanac, which was first developed in Indonesia by Saadoe’ddin Djambek as one of the innovators in hisab thought. One of the ideas proposed by Saadoe’ddin Djambek is the renewal of the calculation of the beginning of the Hijri month. This paper will discuss the calculation of the beginning of the Hijri month in Saadoe’ddin Djambek’s thinking. This research is a literature review with primary data sources from Saadoe’ddin Djambek’s writings and secondary data sources from other writings related to this theme. The data collection method involves documentation, with data analysis using content analysis techniques. The research indicates that Saadoe’ddin Djambek’s approach to calculating the beginning of the Hijri month is a contemporary method, and his data and methodologies play a significant role in determining the onset of the month. The theory of the calculation of the beginning of the month proposed by Saadoe’ddin Djambek provides a relatively new foundation for thinking about the calculation of the beginning of the month at that time, as it is derived from an integrated understanding between experts in calculation and experts in astronomy. Saadoe’ddin Djambek’s calculation method is among those whose accuracy is not significantly different from other methods of calculating the beginning of the month, such as the Ephemeris system. Therefore, this method remains viable for use despite being proposed in the 1970s.